Pelajar Pancasila Sebagai Motor Toleransi di Sekolah - Hernita Purba; Bina Idola Siahaan; Tiur Imeldawati; Goklas J. Manalu (Institut Agama Kristen Negeri Tarutung, 2023)
It is necessary for the younger generation to know that around us, namely in the country of Indonesia, echoes of religious moderation have been voiced in various places. Even in the practice of daily life, moderate life needs to be demonstrated by society. One clear example is the existence of a church that is side by side with a mosque, we are also friends with people of different religions from ours, and there are many other things about tolerance. However, it is not uncommon for us to meet in a formal school environment where students' character is formed for the first time, there are still students who are intolerant of other religions. Like what happened at SMAN 6 Depok, where the chairperson who was elected came from a non-Muslim student, but because the person did not accept it, a vote was held again, this happened last November 2020. But, even though many do not maintain tolerance between religious communities, there are still many groups who accept these differences, such as for example the St. Francis Xavier Catholic High School on the NTT route. Where the student council president of the school is a student from the Muslim religion. This is an alarm that needs to be watched out for, and shows that awareness is needed to have a more moderate religious life, and students in this country can become the driving force for tolerance in their respective schools. Every human being has the basic right to determine the choice of belief he wants to hold. For this reason, as educators it is necessary to build a strong sense of tolerance within students to prevent radicalism among students. This research aims to provide understanding and invite Pancasila students to be able to implement attitudes and a high sense of tolerance for anyone. Perlu untuk generasi muda ketahui bahwa di sekitar kita tinggal yaitu di negara Indonesia ini gaung moderasi beragama sudah disuarakan di berbagai tempat. Dalam praktik kehidupan sehari-hari pun kehidupan moderat perlu ditunjukkan oleh masyarakat. Salah satu contoh nyata adanya gereja yang berdampingan dengan masjid, kita juga berteman dengan orang yang berbeda agama dengan agama kita, dan ada banyak hal tentang toleransi lainnya. Namun, tidak jarang pula kita jumpai di lingkungan sekolah formal di mana karakter siswa dibentuk untuk kali pertama, masih saja ada pelajar yang bersikap intoleran terhadap agama lain. Seperti halnya yang telah terjadi di SMAN 6 Depok, di mana ketua yang terpilih berasal dari siswa non-muslim, tetapi karena oknum yang tidak terima maka diadakan voting (pengambilan suara) kembali, ini terjadi pada November 2020 lalu. Tapi, meskipun banyak yang tidak memelihara toleransi antar umat beragama, masih banyak juga kaum-kaum yang menerima perbedaan itu, seperti contohnya SMA Katolik Santo-Fransiskus Xaverius di Rute NTT. Di mana Ketua OSIS dari sekolah tersebut adalah seorang siswi dari agama Muslim. Hal ini menjadi alarm yang perlu diwaspadai, dan menunjukkan bahwa diperlukannya kesadaran untuk memiliki kehidupan beragama yang lebih moderat, dan pelajar di negeri ini bisa menjadi motor penggerak toleransi di sekolah masing-masing. Setiap manusia memiliki hak asasi untuk menentukan pilihan keyakinan yang ingin dipegang. Untuk itu, sebagai pendidik perlu untuk membangun rasa toleransi yang teguh dalam diri pelajar untuk mencegah radikalisme di kalangan pelajar. Penelitian ini bertujuan untuk memberikan pemahaman serta mengajak para pelajar pancasila agar dapat mengimplementasikan sikap dan rasa toleransi yang tinggi bagi siapa pun.